Salivary Glands: A Brief View on Types, Anatomy & Histological Features - Tariq Soyab (Institute of Medico-legal Publications Pvt Ltd, 2020)
Salivary glands are crucial organs playing a vital role in the secretion of saliva in the oral cavity. Duringits morphogenesis a sequel of coordinated movements that are developmental processes occurred and theinteraction of mesenchyme and epithelium generating the ductal system and secretory units. Salivary glandsconsist of major and minor glands that play different roles in saliva secretion. The maximum cell types ofsalivary glands are innervated by parasympathetic and sympathetic nerves. Histologically serous acini andmucous acini cell types can be seen with a network of the ductal system which includes striated, excretoryand intercalated ducts, the external carotid artery maintain the blood supply of major salivary glands andthe role of vasculature supply remaining unclear regarding the maintenance of saliva secretion which needsfurther investigation. The article throws light on its different types, its histological features, and its ductalsystem.